A middleware solution for integrating and exploring IoT and HPC capabilities. (9th August 2018) - de Souza Cimino, Leonardo; de Resende, José Estevão Eugênio; Silva, Lucas Henrique Moreira; Rocha, Samuel Queiroz Souza; de Oliveira Correia, Matheus; Monteiro, Guilherme Souza; de Souza Fernandes, Gabriel Natã; da Silva Moreira, Renan; de Silva, Junior Guilherme; Santos, Matheus Inácio Batista; Aquino, Andre Luiz Lins; Almeida, André Luís Barroso; et al.
Summary: Even with the considerable advances in the development of middleware solutions, there is still a substantial gap in Internet of Things (IoT) and high‐performance computing (HPC) integration. It is not possible to expose services such as processing, storage, sensing, security, context awareness, and actuating in a unified manner with the existing middleware solutions. The consequence is the utilization of several solutions with their particularities, thus requiring different skills. Besides that, the users have to solve the integration and all heterogeneity issues. To reduce the gap between IoT and HPC technologies, we present the JavaCá&Lá (JCL), a middleware used to help the implementation of distributed user‐applications classified as IoT‐HPC. This ubiquity is possible because JCL incorporates (1) a single application programming interface to program different device categories; (2) the support for different programming models; (3) the interoperability of sensing, processing, storage, and actuating services; (4) the integration with MQTT technology; and (5) security, context awareness, and actions services introduced through JCL application programming interface. Experimental evaluations demonstrated that JCL scales when doing the IoT‐HPC services. Additionally, we identify that customized JCL deployments become an alternative when Java‐Android and vice‐versa code conversion is necessary. The MQTT brokers usually are faster than JCL HashMap sensing storage, but they do not perform distributed, so they cannot handle a huge amount of sensing data. Finally, a short example for monitoring moving objects exemplifies JCL facilities for IoT‐HPC development.